Effect of pain on mood affective disorders in adults with cerebral palsy. (10th May 2020) - Whitney, Daniel G; Bell, Sarah; Whibley, Daniel; Van der Slot, Wilma M A; Hurvitz, Edward A; Haapala, Heidi J; Peterson, Mark D; Warschausky, Seth A
Abstract : Aim: To determine if pain is associated with 12‐month incidence of mood affective disorders (MAD) in adults with cerebral palsy (CP). Method: Data from Optum Clinformatics ® Data Mart (2013–2016) were used for this retrospective cohort study. Diagnostic codes were used to identify adults (≥18y) with CP, incident cases of MAD, and covariates (other neurodevelopmental conditions, sleep disorders, arthritis). Pain (any type, location) was identified between 1st October 2014 and 30th September 2015. The pain group was divided into new or consistent pain if they had a history of pain (i.e. consistent) in the 12 months before their first pain claim date. Crude incidence rates of MAD (expressed per 100 person‐years) were estimated. Cox regression was used to estimate hazard ratio (95% confidence interval [CI]) of MAD after adjusting for covariates. Results: Adults that had new pain ( n =859; incidence rate=15.5) or consistent pain ( n =1303; incidence rate=17.9) had greater crude incidence rate of MAD compared to adults without pain ( n =3726; incidence rate=5.9). The elevated rate of MAD remained after adjusting for covariates, for new pain (hazard ratio=2.4; 95% CI=1.9–3.0) and consistent pain (hazard ratio=2.1; 95% CI=1.7–2.7). Interpretation: Pain is associated with greater incidence of MAD in adults with CP. This association remained after accounting for potential confounding factors. What this paper adds: Pain was associated with higher 12‐month incidence of mood affective disorders (MAD). The 12‐month MAD incidence was similar between new and consistent pain groups. The MAD incidence remained higher adjusting for neurodevelopmental comorbidities, sleep disorders, and arthritis. What this paper adds: Pain was associated with higher 12‐month incidence of mood affective disorders (MAD). The 12‐month MAD incidence was similar between new and consistent pain groups. The MAD incidence remained higher adjusting for neurodevelopmental comorbidities, sleep disorders, and arthritis. This article is commented on by Grandidge and Nair on page 887 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Efecto del dolor sobre los trastornos afectivos del ánimo en adultos con parálisis cerebral: Objetivo: Determinar si el dolor está asociado con una incidencia de 12 meses de trastornos afectivos del ánimo (TAA) en adultos con parálisis cerebral (PC). Método: Se utilizaron los datos de Optum Clinformatics ® Data Mart (2013‐2016) para este estudio de cohorte retrospectivo. Se utilizaron códigos de diagnóstico para identificar adultos (≥18 años) con PC, casos incidentes de TAA y covariables (otras afecciones del desarrollo neurológico, trastornos del sueño, artritis). El dolor (cualquier tipo, ubicación) se identificó entre el 1 de octubre de 2014 y el 30 de septiembre de 2015. El grupo de dolor se dividió en dolor nuevo o constante si tenían antecedentes de dolor (p.e. consistente) en los 12 meses anteriores a su primera fecha de reclamo de dolor. Se estimaron las tasas brutas de incidencia de TAA (expresadas por 100 años‐persona). Se utilizó la regresión de Cox para estimar el cociente de riesgo (intervalo de confianza [IC] del 95%) de TAA después de ajustar por covariables. Resultados: Los adultos que tenían dolor nuevo ( n = 859; tasa de incidencia = 15.5) o dolor constante ( n = 1303; tasa de incidencia = 17.9) tuvieron una tasa de incidencia bruta mayor de TAA en comparación con los adultos sin dolor ( n = 3726; tasa de incidencia = 5.9 ) La tasa elevada de TAA permaneció después de ajustar por covariables, para dolor nuevo (cociente de riesgo = 2.4; IC 95% = 1.9–3.0) y dolor constante (cociente de riesgo = 2.1; IC 95% = 1.7–2.7). Interpretación: El dolor se asocia con una mayor incidencia de TAA en adultos con PC. Esta asociación se mantuvo después de tener en cuenta los posibles factores de confusión. Efeito da dor nos transtornos afetivos do humor em adultos com paralisia cerebral: Objetivo: Determinar se a dor é associada com a incidência de transtornos afetivos do humor (TAH) em adultos com paralisia cerebral (PC). Método: Dados da Optum Clinformatics ® Data Mart (2013–2016) foram usados para este estudo de coorte retrospectivo. Códigos diagnósticos foram usados para identificar adultos (≥18a) com PC, casos incidentes de TAH, e covariáveis (outras condições neurodesenvolvimentais, desordens do sono, artrite). A dor (qualquer tipo, local) foi identificada entre 1o de outubro de 2014 e 30 de setembro de 2015. O grupo com dor foi dividido em dor nova ou consistente se tivesse historia de dor (consistente) nos 12 meses antes da primeira da data do primeiro atendimento com queixa de dor. Taxas de incidência de TAH (expressas por 100 pessoas/ano foram estimadas. Regressão de Cox foi usada para estimar a taxa de risco (intervalo de confiança [IC] a 95% de TAH após ajustar para covariáveis. Resultados: Adultos que tiveram dor nova ( n =859; taxa de incidência=15, 5) ou consistente ( n =1303; taxa de incidência=17, 9) tiveram maior incidência geral de TAH comparados com os adultos sem dor ( n =3726; taxa de incidência=5, 9). A elevada taxa de TAH permaneceu após ajustar para covariáveis, para a dor nova (taxa de risco=2, 4; IC 95% =1, 9–3, 0) e consistente (taxa de risco=2, 1; IC 95% =1, 7–2, 7). Interpretação: A dor é associada com maior incidência de TAH em adultos com PC. A associação permaneceu após considerar potenciais fatores de confusão.